Modulation by NPY/NPF-like receptor underlies experience-dependent, sexually dimorphic learning - Sonu Peedikayil-Kurien; Rizwanul Haque; Asaf Gat; Meital Oren-Suissa (Nature Communications)
Abstract The evolutionary paths taken by each sex within a given species sometimes diverge, resulting in behavioral differences. Given their distinct needs, the mechanism by which each sex learns from a shared experience is still an open question. Here, we reveal sexual dimorphism in learning: C. elegans males do not learn to avoid the pathogenic bacteria PA14 as efficiently and rapidly as hermaphrodites. Notably, neuronal activity following pathogen exposure was dimorphic: hermaphrodites generate robust representations, while males, in line with their behavior, exhibit contrasting representations. Transcriptomic and behavioral analysis revealed that the neuropeptide receptor npr-5, an ortholog of the mammalian NPY/NPF-like receptor, regulates male learning by modulating neuronal activity. Furthermore, we show the dependency of the males’ decision-making on their sexual status and demonstrate the role of npr-5 as a modulator of incoming sensory cues. Taken together, these findings illustrate how neuromodulators drive sex-specific behavioral plasticity in response to a shared experience.